Bridging the Gap Between Physical Health and Autism Spectrum Disorder - Sala R (Dove Medical Press, 2020)
Regina Sala,1 Lorene Amet,2 Natasa Blagojevic-Stokic,3 Paul Shattock,4 Paul Whiteley5 1Centre for Psychiatry, Wolfson Institute, Barts & The London School of Medicine & Dentistry Queen Mary University of London, London, UK; 2Autism Treatment Plus, Edinburgh, UK; 3Thinking Autism, London, UK; 4Education & Services for People with Autism, Sunderland, UK; 5Education & Services for People with Autism Research, Sunderland, UKCorrespondence: Dr Regina SalaCentre for Psychiatry, Wolfson Institute, Barts & The London School of Medicine & Dentistry Queen Mary University of London, London, UKEmail regina.sala@nhs.netAbstract: Autism spectrum disorder (ASD) is a highly complex and heterogeneous developmental disorder that affects how individuals communicate with other people and relate to the world around them. Research and clinical focus on the behavioural and cognitive manifestations of ASD, whilst important, have obscured the recognition that ASD is also commonly associated with a range of physical and mental health conditions. Many physical conditions appear with greater frequency in individuals with ASD compared to non-ASD populations. These can contribute to a worsening of social communication and behaviour, lower quality of life, higher morbidity and premature mortality. We highlight some of the key physical comorbidities affecting the immune and the gastrointestinal systems, metabolism and brain function in ASD. We discuss how healthcare professionals working with individuals with ASD and parents/carers have a duty to recognise their needs in order to improve their overall health and wellbeing, deliver equality in their healthcare experiences and reduce the likelihood of morbidity and early mortality associated with the condition.Keywords: autism spectrum disorder, ASD, physical health, comorbidity, inequality